Dampak Resistensi Antibiotik terhadap Kesehatan Masyarakat di Negara Berkembang dan Upaya Pencegahannya untuk Meningkatkan Kualitas Kesehatan Global - Kadek Risa Apriani; Ketut Widyani Astuti (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
Antimicrobial resistance (AMR) poses a major global health threat, with severe impacts in developing countries due to weak health systems, poor regulation, and low sanitation standards. This review summarizes 12 studies from Asia and Africa on AMR’s clinical, social, economic, and environmental effects. AMR leads to first-line treatment failure, prolonged hospital stays, increased morbidity and mortality, and necessitates costly, toxic last-line antibiotics. Economic consequences include higher treatment costs, productivity loss, and poverty risk from high medical expenses. Environmental contributors such as contamination from medical waste, livestock, and the food industry accelerate resistant bacteria spread. Effective control requires integrated strategies, including Antimicrobial Stewardship Programs (ASP) based on AWaRe classification, laboratory strengthening, One Health approaches, public education, strict antibiotic distribution regulations, and cross-sector monitoring. These measures aim to curb AMR progression and reduce health burdens in developing nations. The rise of AMR further complicates healthcare delivery in countries already struggling with limited resources and underfunded healthcare systems. The growing prevalence of multidrug-resistant (MDR) and extensively drug-resistant (XDR) organisms threatens the effectiveness of current medical treatments, including those for common infections such as tuberculosis and pneumonia. Infections that were once easily treatable with antibiotics are now leading to longer and more complicated hospitalizations, greater healthcare costs, and higher death rates. Additionally, the lack of access to newer, more effective antibiotics and diagnostic tools makes managing resistant infections in these regions even more challenging. Environmental factors, particularly contamination from healthcare facilities and agricultural practices, play a key role in the proliferation of resistant pathogens.